FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUASAN KONSUMEN TERHADAP LAYANAN PAYMENT POINT ONLINE BANK (PPOB) - Datuamas, Annisah A (CAM JOURNAL, Jurnal Agen Perubahan Manajemen, 2019)
This study aims to analyze the factors that influence customer satisfaction with the payment of electricity and water bills for PDAMs at PT Nusa Mandiri. Methods of collecting data using a questionnaire distributed to 100 consumers of PT. Nusa Mandiri Berau District. The analysis tools used are Validity Test, Reliability Test, Multiple Linear Regression Analysis, t Test and F Test. The results of this study indicate that the factors that have a significant ef ect on customer satisfaction are Service Quality, Responsiveness, Empathy, Tangible. Whereas reability and assurance do not significantly influence customer satisfaction.